Canada-wide mixed methods analysis evaluating the reasons for inappropriate emergency department presentation in patients with a history of atrial fibrillation: the multicentre AF-ED trial. Issue 4 (16th April 2020) - Hong, Kathryn Lauren; Babiolakis, Corinne; Zile, Brigita; Bullen, Milena; Haseeb, Sohaib; Halperin, Frank; Hohl, Corinne M; Magee, Kirk; Sandhu, Roopinder K; Tian, Simon Yu; Kennedy, Ashley; Lobban, Trudie; et al.
Abstract : Objectives: The primary objective of this study was to ascertain the reasons for emergency department (ED) attendance among patients with a history of atrial fibrillation (AF). Design: Appropriate ED attendance was defined by the requirement for an electrical or chemical cardioversion and/or an attendance resulting in hospitalisation or administration of intravenous medications for ventricular rate control. Quantitative and qualitative responses were recorded and analysed using descriptive statistics and content analysis, respectively. Random effects logistic regression was performed to estimate the OR of inappropriate ED attendance based on clinically relevant patient characteristics. Participants: Participants ≥18 years with a documented history of AF were approached in one of eight centres partaking in the study across Canada (Ontario, Nova Scotia, Alberta and British Columbia). Results: Of the 356 patients enrolled (67±13, 45% female), the majority (271/356, 76%) had inappropriate reasons for presentation and did not require urgent ED treatment. Approximately 50% of patients(172/356, 48%) were driven to the ED due to symptoms, while the remainder presented on the basis of general fear or anxiety (67/356, 19%) or prior medical advice (117/356, 33%). Random effects logistic regression analysis showed that patients with a history of congestive heart failure were significantly more likely to seek urgent care for appropriate reasons (p=0.03). Likewise, symptom-related concerns for ED presentation were significantly less likely to result in inappropriate visitation (p=0.02). When patients were surveyed on alternatives to ED care, the highest proportion of responses among both groups was in favour of specialised rapid assessment outpatient clinics (186/356, 52%). Qualitative content analysis confirmed these results. Conclusions: Improved education focused on symptom management and alleviating disease-related anxiety as well as the institution of rapid access arrhythmias clinics may reduce the need for unnecessary healthcare utilisation in the ED and subsequent hospitalisation. Trial registration number: NCT03127085